The Ins and Outs of B Cells in Multiple Sclerosis - Blauth, Kevin; Owens, Gregory P.; Bennett, Jeffrey L. (Frontiers in Immunology, 2015)
B cells play a central role in multiple sclerosis (MS) pathology. B and plasma cells may contribute to disease activity through multiple mechanisms: antigen presentation, cytokine secretion, or antibody production. Molecular analyses of B cell populations in MS patients have revealed significant overlaps between peripheral lymphoid and clonally expanded central nervous system (CNS) B cell populations indicating that B cell trafficking may play a critical role in driving MS exacerbations. In this review, we will assess our current knowledge of the mechanisms and pathways governing B cell migration into the CNS and examine evidence for and against a compartmentalized B cell response driving progressive MS pathology.